The nexus between tourism and urban risk: Towards inclusive, safe, resilient and sustainable outdoor tourism in African cities. (March 2020) - Musavengane, Regis; Siakwah, Pius; Leonard, Llewellyn
Abstract: Sub-Saharan Africa is set to increase its tourism sector in urban areas. However, its cities are also settings for numerous struggles over future developments coupled with excess urban risks. The nexus created by the relationship between urbanization, urban growth, urban governance, poverty and inequality, and ecological degradation is altering the sustainability of urban tourism in Sub-Saharan African cities. Inspired by the United Nations' 2030 Sustainable Development Goal 11; making cities and human settlements inclusive, safe, resilient and sustainable, this study critically analyses the linkages between risk, justice, inclusion, trust and power relations in urban spaces with the aim to strengthen tourism governance in Sub-Saharan African urban settings. Document analysis is adopted to draw evidence and critically analyse the sustainability of tourism in the three Sub-Saharan cities: Accra, Ghana; Johannesburg, South Africa; and Harare, Zimbabwe. The study reveals that tourism development in Africa is dominantly underpinned by neoliberal development strategies which threaten the sustainability of tourism in African cities. It, therefore, argues for good governance through strong sustainability institutions which strengthen the regulative mechanisms, processes and organizational culture which empowers local communities. Sustainable tourism approaches that are resilient centred have a potential to promote urban tourism in Sub-Saharan African cities.